We saw in Spain (pamphlet) - Dugdale, John ; Wilkinson, Ellen Cicely, 1891-1947 ; Noel-Baker, Philip Noel-Baker, Baron ; Malindine, E. G.; Attlee, Clement, 1883-1967
1937 The Fascists Cannot Win Now By PHILIP NOEL BAKER, M.P. MY dominant impressions of our visit to Spain are three: The political strength of the Republican Government, The efficiency of its administration, and the bitter resentment caused by the policy which is miscalled "Non-Intervention." The political support for the Government is wider and stronger than I had expected. It includes people whose views differ on everything but their belief in democracy. It includes, contrary to popular belief, a vast number of fervent adherents of the Roman Catholic faith. I had a long discussion on the religious question with the member of the Cabinet responsible. Senor Irujo, the Minister of Justice. He is himself a Roman Catholic. So is General Rojo, the Chief of the General Staff. So are many leading people in the Army and the administration. An officer at a training school asked permission of his colonel to talk to me in private; he told me that all his family were ardent Catholics, that he and four of his brothers were officers in the Government Army, and that "the vast majority of all Catholics of good faith" were on the Government side. He said it was their sacred duty to "save the democratic Constitution," for without parliamentary democracy Spain would be headed for disaster. The same belief was expressed to me on every hand. It is this belief which explains the extent and the vigour of the political support which the Government has obtained. Every Party which helped to create the Republic has remained loyal to its cause; and many people of other Parties have given their help. Even the Prime Minister of the Government which was defeated by the Frente Popular in the General Elections of February, 1935, attended the Cortes in October last to give his full support to the Republic and to attest to the validity of the present Government's powers. The contrast in this regard with General Franco's "Government" is striking. It would puzzle his warmest friends to say which of the Parties in the Cortes is on his side. Gil Robles, who is the leader of the largest Party of the Right, and who was regarded before the General Elections as the "strong man" of Spain, is not only not a member of General Franco's "Government," he is a refugee in Portugal, playing no part in the "Nationalist" movement of any kind. The last thing I expected to find in Republican Spain was efficient administration. I remembered that eighteen months ago the Army, the police, every Government department, and every local service had been reduced to chaos by the Rebellion. I thought it certain that the reconstruction would be a slow affair; I expected the kind of standards to which I have been accustomed in other Mediterranean lands. I was not only surprised, therefore, I was amazed by what we saw. In every domain of Government activity - the refugee offices, the food administration, the control of agriculture, the schools, the repair of roads, the organisation of transport, the air-raids precautions, the hospitals, the Army training - the standard of efficiency was very high. "Do it now" has replaced the "manana" of days gone by. "Non-Intervention" - the very phrase provokes a storm of protest whenever it is used. The Spanish people find it impossible to understand how the British nation have agreed to such a dangerous farce. They have never asked for, and they do not desire, our intervention. They only ask to be allowed to exercise their legal right to buy arms from private firms in democratic countries to defend themselves against the arms (and armies) which Herr Hitler and Signor Mussolini have been pouring in. When you see the German "Junkers" carrying out their daily bombing raids, and when you remember the vast armament which the fascist dictators have sent to Spain, it is easy to understand the sense of grave injustice which the Spaniards feel. When I tried to explain the British Government's defence to a Catholic statesman who now holds a position of high responsibility in Republican Spain, he said: "Tell the British Government from me that there is a more bitter hatred in Spain to-day against Great Britain than there is against Italy." He utterly scouted the suggestion that to sell the Government arms would involve the slightest risk of general war. And looking back upon the full success of the far more perilous action which the Nyon plan involved, I find it impossible to doubt that he is right. "Non-Intervention" has not reduced the risks of general war; it has enormously increased them, for it has prolonged the Spanish struggle and roused passions and ambitions that are dangerous to us all. We stood by King Alfonso's palace in Madrid, badly scarred by Fascist artillery. We looked out across the barricades, across the line of trenches to the royal park, where the Moors made their desperate onslaught in November, 1936. As we stood there, I pictured in my mind the untrained Trade Union levies, who took shotguns, sticks and knives into battle against those magnificent Moroccan troops. Madrid was saved then by the courage of her people, in spite of all that the Non-Intervention Committee did to handicap them. If General Franco could not then break their resistance, I am certain that he cannot now break the strong and resolute Republic which has since been forged. "HOME-COMING 1937." After the bombers come to Barcelona. LABOUR DEMANDS JUSTICE FOR REPUBLICAN SPAIN 292/946/18a/69(vi)